On the Analysis of Groupware Usability Using Annotated GOMS - Antunes, Pedro (2009)
GOMS is a well-known model that has been successfully used in predicting the performance of human-computer interaction, identifying usability problems and improving user-interface design. The focus of GOMS is on the individual user, however. This explains why it has no significant impact in the groupware context. This paper discusses the applicability of GOMS in the groupware context. We analyzed the impact of groupware in the cognitive architecture of GOMS in order to accomplish this goal. The obtained results led us to introduce an annotation scheme in GOMS reflecting several pre and post conditions necessary to describe how operations realized by collaborating users are interrelated in GOMS descriptions. We discuss the applicability of Annotated GOMS by studying a collaborative tool for software engineering requirements negotiation. This work contributes to the collaboration systems field with an innovative way to analyze groupware usability